The challenge of treating elderly patients with advanced bone and soft tissue sarcomas - Kasper, Bernd; Hohenberger, Peter (Critical reviews in oncology, hematology, 2020)
Soft tissue sarcomas in elderly patients beyond the age of 65 years account for almost 50 % of the sarcomas of the total patient population in this rare tumor entity. Distinct clinical and biological characteristics of the different sarcoma subtypes have to be taken into account in the various age groups. Old age should not per se be a contraindication to chemotherapy administration or to undergo surgery; however, particular aspects regarding safety, comorbidities, toxicity, and quality of life have to be considered. The use of a geriatric assessment and especially the use of predictive tools for estimating the expected toxicity may be helpful in this challenging situation. On the other side, osteosarcomas in the elderly patient population represent an extreme rarity. The adequate primary surgical care of these patients seems crucial in terms of prognosis as the addition of chemotherapy does not significantly improve patients’ overall survival.